Analysis of national cultural distance for Malaysian and Indonesian acquirers: A cross-border mergers and acquisitions perspective - Jedin, Mohd. Haniff; Md Saad, Norsafinas (2012)
This article attempts to provide evidence of the national cultural distance between Malaysian and Indonesian acquirers and twenty-nine countries worldwide using a survey.Thomson One Banker is used as the main database covering completed Malaysian and Indonesian cross-border M&As by Malaysian firms are most likely to succeed when the target is an Indonesian firms due to greater understanding and hence collaboration between the two.Likewise, out of the countries investigated, Malaysian targets are found to have the smallest cultural distance from Indonesian acquirers.These results may be strengthened by the fact that the two are neighbouring countries and have similar languages and cultures, particularly in terms of religious aspects.The study also reveals that the Japanese targets are at the greatest cultural distance from the Malaysian acquirers.Meanwhile, the Thai targets are at the greatest cultural distance from the Indonesian acquirers but have the second smallest cultural distance from the Malaysian acquirers.